MOF based coated adsorption system for water desalination and cooling integrated with Pre-treatment unit. (March 2023) - Albaik, Ibrahim; Diab, Kamal E.; Saleh, Majdi; Al-Dadah, Raya; Mahmoud, Saad; Elsheniti, Mahmoud B.; Solmaz, İsmail and Salama, Eslam and Shokry Hassan, H. and Elkadi, Marwa F.
Highlights: Hybrid adsorption water pre-treatment and desalination system is investigated. A MOF coating thickness of 0.75 mm is applied on the heat exchanger surfaces. Zeolite, activated carbon and aluminium fumarate are used in the hybrid system. The evaporator and condenser of the desalination unit are optimized. Abstract: Recently, the adsorption technologies received significant interest for water purification and desalination application as well as for clean cooling production, since they offer an environmentally friendly solution using low-grade energy compared to the conventional systems. In this work, a hybrid adsorption system based on combining a pre-treatment unit for heavy metal removal with a desalination and cooling unit is experimentally investigated. Activated carbon and zeolite in powder and beads forms have been used in pre-treatment unit as adsorbent materials for the removal of iron, lead, manganese and nickel from ground water, while a coating form of aluminium fumarate MOF adsorbent material is used in heat powered adsorption heat pump for desalination and cooling unit. For the formation of activated carbon/zeolite beads, 45 % polymer loading showed the highest efficiency for the removal of the heavy metals which reached 87 % of iron. After taking the purified water from the pretreatment unit, the desalination and cooling unit produced higher than 260L/day of distilled water and 6.9 kW of cooling power with a coefficient of performance of 0.26 using a coating thickness of 0.75 mm on the wire finned tube heat exchanger adsorber beds. With the hybrid system, a practical mitigation of the accumulation of some chemical compounds on the evaporator surface with continuous operation was achieved. The effect of evaporator and condenser chamber volumes are investigated to minimize the compactness of the MOF adsorption heat pump. This hybrid adsorption system demonstrates a promising solution for pure water and cooling production over the conventional available ones.